A numerical study on seasonal transport variability of the North Indian Ocean boundary currents using Regional Ocean Modeling System (ROMS). Issue 1 (2nd January 2022) - Sen, Radharani; Pandey, Suchita; Dandapat, Sumit; Francis, P. A.; Chakraborty, Arun
ABSTRACT: This study investigates the seasonal transport variability of the North Indian Ocean (NIO) boundary currents, in particular, the East India Coastal Current (EICC) in the Bay of Bengal (BoB), West India Coastal Current (WICC) in the Arabian Sea (AS) and Somali Current (SC) in the Equatorial Indian Ocean (EIO) using a high-resolution Regional Ocean Modeling System (ROMS) with climatological river input. The simulation result indicates that northward EICC peaks in March and its mean transport is 2.65 Sv during February to April. The southward EICC extends down to 200 m depth and transports 0.67 Sv during October–December. Northward WICC which extends down to 100 m depth transports 0.31 Sv along the west coast of India during the winter monsoon. Southwestward SC flows between 6.5°N to 3°N, and northeastward cross-equatorial SC goes up to 11°N along the Somali coast. Northeastward SC which is the strongest coastal current in the NIO transports 13.05 Sv during the summer monsoon. The average transport of southwestward SC is 2.57 Sv only. The study suggests that wind stress and wind stress curl (WSC) plays a vital role in the semiannual reversal of transport and remote forcing modulated by equatorial wind anomalies dominates the southward EICC transport.